BUDIDAYA MAGGOT BSF UNTUK PAKAN TERNAK SKALA RUMAHTANGGA DI JALAN RINDUNG, KELURAHAN BANE, PEMATANG SIANTAR - Romauli Simanjuntak; Roeskani Sinaga; Ramainim Saragih; Wahyunita Sitinjak; Rosmadelina Purba; Arvita Sihaloho; Cristin Imelda Girsang; Linda Reni Purba; Mirna Anriani Siregar; January Rizky; Simon Sidabukke (Lembaga Pengabdian Masyarakat Universitas Simalungun, 2022)
The increase in the price of animal feed makes it difficult for households as farmers by utilizing household waste to feed their livestock. The increase in feed prices also encourages food farmers to switch to corn because corn is a raw material for animal feed. So that household farmers also have difficulty buying corn. Maggot BSF is an alternative feed that is very high in protein to encourage livestock growth. BSF maggots are larvae that can be used as alternative feed. Cultivation of BSF maggot is also relatively easy and can utilize household waste or food scraps as BSF maggot food. In this community service, training activities for maggot cultivation as an alternative to animal feed are carried out in Bane Village. The implementation method is carried out by means of lectures, discussions and practice. The result of this service is to grow the participants' desire to cultivate BSF maggot as animal feed. The result was that the participants were very responsive to this activity, as evidenced by the active participation of the community in the activity from beginning to end and the large number of active participants in the discussion and question and answer sessions. So it can be concluded that the maggot cultivation training in Bane Village was successful and the participants' understanding and attitudes increased about the importance of waste treatment for maggot cultivation as an alternative to animal feed